Gambaran Usia Menarche dan Kejadian Dismenore Primer pada Siswi SMA di Kecamatan Sale Rembang - Aprilia Qoulan Syakila; Endang Nur Widyaningsih (HB PRESS, 2023)
Adolescent girls who were experiencing menstruation often experienced primary dysmenorrhea. Primary dysmenorrhea can be triggered by early menarche. Based on the preliminary survey that has been carried out, it is known that 80% of high school students in Sale District of Rembang were experiencing primary dysmenorrhea. This study aimed to determine the description between the age of menarche and the incidence of primary dysmenorrhea in high school students in Sale District of Rembang. The type of research used was observational with a cross sectional approach. Age of menarche was obtained by filling a questionnaire and the incidence of primary dysmenorrhea through filling a Numeric Rating Scale questionnaire. The sampling was using simple random sampling techniques with research subjects obtained as many as 59 people. The statistical test used to determine the correlation between variables are a chi-square test. The results of the univariate analysis obtained on the age of early menarche was 27,1% and the female students who were experiencing primary dysmenorrhea was 79,7%. The results of the bivariate analysis on the age of menarche, a p-value of 0,018 (p<0,05) was shown. There was a significant correlation between the age of menarche and the incidence of primary dysmenorrhea in high school students in Sale District of Rembang. The research suggests that providing counselling about women's reproductive health and the importance of implementing a healthy lifestyle should be given to high school students.